2007
DOI: 10.1590/s1135-57272007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Nutrición y síndrome metabólico

Abstract: Efecto del tratamiento de dos días con orlistat sobre los niveles de leptina plasmática en pacientes obesas sin pérdida de peso Resumen Objetivo: poco se conoce sobre el impacto de orlistat en el sistema leptina. Estudiamos la respuesta de la leptina plasmática y la sensación de saciedad tras dos días de tratamiento con orlistat sin dieta hipocalórica ni pérdida de peso. Material y métodos: reclutamos veinte mujeres obesas en nuestras consultas externas de medicina. Habían recibido restricción dietética y modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 102 publications
0
4
0
6
Order By: Relevance
“…Although SCAT has been associated with blood pressure and, in fact, the above mentioned pathways are strongly related to endothelial dysfunction [4], the significance was lost after the adjustments. Various studies have shown that, the increase of free fat acid in circulation corroborates with formation of low density lipoproteins (LDL) e very low density lipoproteins (VLDL) associated to reduction on high density lipoproteins (HDL) and very high density lipoproteins (VHDL), which results in atherosclerosis and elevation of arterial pressure [28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Although SCAT has been associated with blood pressure and, in fact, the above mentioned pathways are strongly related to endothelial dysfunction [4], the significance was lost after the adjustments. Various studies have shown that, the increase of free fat acid in circulation corroborates with formation of low density lipoproteins (LDL) e very low density lipoproteins (VLDL) associated to reduction on high density lipoproteins (HDL) and very high density lipoproteins (VHDL), which results in atherosclerosis and elevation of arterial pressure [28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Estudios realizados a grupos de pacientes diabéticos y con síndrome metabólico presentan que la dieta más óptima para disminuir niveles de glucosa y riesgo cardiovascular es la dieta rica en verduras, frutas, fibra no refinada, aumento de ingesta en grasas mono y poliinsaturadas, así como en pescado, micronutrientes y aceite de olivo; además de disminuir ingesta de grasas saturadas y de alimentos de alto índice glucémico, así como de sodio y azúcares refinados. Todo esto apegado estrechamente a una buena actividad física ya que disminuye la resistencia a la insulina (12,13).…”
Section: Discussionunclassified
“…23 The prolonged intake of food with a high GL is related to insulin resistance, whether due to the loss of pancreatic function, or the excessive production of insulin, or to the glucotoxicity of beta cells. 8 Therefore, it is important to assess the consumption of carbohydrates in the diet of children and adolescents, considering their quantity and quality, with the aim of preventing future problems, such as MS, and a potential chronic disease.…”
Section: Glycemic Load and Metabolic Syndromementioning
confidence: 99%